PENERAPAN TEKNOLOGI PEMBANGKIT LISTRIK TENAGA SURYA SEBAGAI SUMBER LISTRIK CADANGAN DI PONDOK PESANTREN HIDAYATULLAH YOGYAKARTA - Marausna, Gaguk; Wahyu Murdiyanto, Aris; Rizki Putra, Ikbal; Eko Prasetiyo, Erwan; Yulianto Prabowo, Fajar (Universitas PGRI Yogyakarta, 2024)
The application of solar power plant technology as a backup power source at Hidayatullah Islamic Boarding School, Yogyakarta, aims to address the challenges caused by disrupted electricity supply. This Islamic boarding school has a strategic location due to its close access to the city center of Yogyakarta. The school relies on electricity for its educational and worship activities. A study was conducted to assess the potential of solar energy, geographical conditions, and the readiness of Hidayatullah Islamic Boarding School to adopt renewable energy technology. After the assessment, structured implementation activities, such as awareness socialization, training, and direct assistance, were carried out to ensure the management of the solar power system by the school administration. The results of the Community Service program showed that a solar power system had successfully been implemented to address disruptions during power outages, thereby improving worship and educational activities. This program encourages partner involvement and environmental awareness among the school management and students. Recommendations for ensuring the program’s sustainability include training, routine performance evaluations, and potential partnerships with government and private organizations to promote the use of renewable energy. This successful program is expected to serve as a model for other educational institutions seeking to implement renewable energy technology. Keyword: energy, solar, power plant, backup, community service.